2002
DOI: 10.5194/angeo-20-1539-2002
|View full text |Cite
|
Sign up to set email alerts
|

Cusp-latitude Pc3 spectra: band-limited and power-law components

Abstract: Abstract. This work attempts to fill a gap in comparative studies of upstream-generated Pc3-4 waves and broad band ULF noise observed at cusp latitudes. We performed a statistical analysis of the spectral properties of three years of cusp-latitude ground magnetometer data, finding that the average daytime Pc3-4 spectra are characterized by two principal components: an upstream-related band-limited enhancement ('signal') and a power-law background ('noise') with S(f ) ∝ f −4 . Based on this information we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 36 publications
2
44
4
Order By: Relevance
“…Out of 121 daily magnetic records, 23 were excluded due to disturbed conditions. In contrast to the radar data, magnetic spectra show a single near-noon peak, in agreement with findings by Villante et al [2000] and Ponomarenko et al [2002] at polar cap and cusp latitudes, respectively.…”
Section: Diurnal Trendcontrasting
confidence: 49%
See 2 more Smart Citations
“…Out of 121 daily magnetic records, 23 were excluded due to disturbed conditions. In contrast to the radar data, magnetic spectra show a single near-noon peak, in agreement with findings by Villante et al [2000] and Ponomarenko et al [2002] at polar cap and cusp latitudes, respectively.…”
Section: Diurnal Trendcontrasting
confidence: 49%
“…The power spectrum lacks the typical bandlimited component at f '10-50 mHz [Ponomarenko et al, 2002[Ponomarenko et al, , 2005 and instead shows a lower frequency plateau followed by a power law decrease at f 10 mHz;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engebretson et al, 1986;Takahashi and Anderson, 1992;Ponomarenko et al, 2002). On the ground, maximum Pc3-4 power occurs around auroral/cusp latitudes (Fraser-Smith, 1982;Bol'shakova and Troitskaya, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…Ground-based statistical studies (e.g. Ponomarenko et al, 2002) have revealed that at high latitudes Pc3-4 pulsations comprise two principal components: a band-limited enhancement ("signal") usually centered around 20-30 mHz; and a power-law background ("noise") with power spectral density ∝f −p , where p 3−4. The signal spectrum probably relates to the upstream source (Ponomarenko et al, 2002).…”
Section: Introductionmentioning
confidence: 99%